Slavery without Slaves? The Legal Slavery in Plato’s Laws - Etienne Helmer (Miscelánea Comillas, 2019)
The contemporary scholarly exegesis on the ancient Greek thought on slavery only examines whether some philosophers denounced this institution or not. As to the significance that they may have given to it, it is rarely raised. Contrary to this tendency, this paper will examine how Plato in the Laws reveals the political significance of slavery: far from admitting it for cultural or natural reasons, he considers it a necessary category to demarcate the civic space from its outside. Such a «slavery without slaves» operates as a political frontier.